Privilege and Property Essays on the History of Copyright - Bently, Lionel; Deazley, Ronan; Kretschmer, Martin (Open Book Publishers, 2010)
What can and can't be copied is a matter of law, but also of aesthetics, culture, and economics. The act of copying, and the creation and transaction of rights relating to it, evokes fundamental notions of communication and censorship, of authorship and ownership-of privilege and property. This volume conceives a new history of copyright law that has its roots in a wide range of norms and practices. The essays reach back to the very material world of craftsmanship and mechanical inventions of Renaissance Italy where, in 1469, the German master printer Johannes of Speyer obtained a five-year exclusive privilege to print in Venice and its dominions. Along the intellectual journey that follows, we encounter John Milton who, in 1644 accused the English parliament of having been deceived by the 'fraud of some old patentees and monopolizers in the trade of bookselling' (i.e. the London Stationers' Company). Later revisionary essays investigate the regulation of the printing press in the North American colonies as a provincial and somewhat crude version of European precedents, and how, in the revolutionary France of 1789, the subtle balance that the royal decrees had established between the interests of the author, the bookseller, and the public, was shattered by the abolition of the privilege system. Some of the essays also address the specific evolution of rights associated with the visual and performing arts. The volume is a companion to the digital archive Primary Sources on Copyright (1450-1900), funded by the UK Arts and Humanities Research Council (AHRC). Privilege and Property is recommended in the Times Higher Education Textbook Guide (November, 2010).